Family Support Relationship With Playing Activities Of 5-6 Years Old Children At Pandemic Time At TK IDATHA I - Tenriwati; Alfira, Nadia; Andi Azifa Adillah Amhar (Jurnal Life Birth, 2020)
Play and children are an inseparable unity. Every activity carried out by children will always indicate play activities. Playing is very important for early childhood because through play it develops aspects of child development. The importance of fulfilling play when children are at home requires full support from the family to improve children's development in all aspects considering that at this time children's schools are closed and children's activities must be fully carried out at home. This research design used a cross-sectional study design. The sampling method used was nonprobability sampling, namely a purposive sampling technique. The research sample was 36 respondents. The research was conducted in August. Research by measuring or observing at the same time (Point Time Approach). The results of the study, namely the results of fisher's alternative chi-square test obtained p-value = 0.008 in the sense that the p-value is smaller than the value of Î± = 0.05. There is a significant relationship between family support and children's play activities. It is hoped that this research can become information material for parents in accompanying their children during the pandemic and always accompanying children while playing both during the pandemic period and after the pandemic has passed.